Ecological network construction for bird communities in high-density urban areas: A perspective of integrated approaches - Honghui Yang; Weizhen Xu; Zhengyan Chen; Xinqi Xie; Jiao Yu; Xinyi Lei; Shan Guo; Zheng Ding (Ecological Indicators, 2024)
With the rapid pace of global urbanization, the conflict between the needs of human economic development and ecological conservation is becoming increasingly prominent. As an important habitat along the global migratory routes of migratory birds in East Asia, the construction of an ecological network for the bird communities in Foshan City is essential to protect urban biodiversity. In this research, we employs the Maximum Entropy Model (MaxEnt) and the Remote Sensing Ecological Index (RSEI) to identify ecological source sites in Foshan City based on bird migration characteristics and habitat requirements, and calculated the minimum threshold for the area of ecological source area by using the granularity inverse method. Secondly, the entropy weight method (EWM) and the analytical hierarchy process (AHP) are combined to establish a comprehensive resistance surface. Finally, circuit theory and hydrological analysis principles are utilized to construct ecological network. The findings reveal the following: The landscape component structure is best at a grain size of 1400 m, and a minimum threshold area of 1.96 km2 is identified for ecological sources in Foshan. A total of 19 ecological sources, spanning a combined area of 636.09 km2, have been identified. These sites are mainly clustered in the north, south-west and east of Foshan City. In terms of ecological corridors, this research shows the existence of 51 corridors with a total length of 501.84 km. These corridors include 7 first-level corridors, 25 s-level corridors, and 19 potential corridors (including 15 radiating routes). At the same time, we identified 88 ecological nodes, including 10 critical ecological nodes and 78 general ecological nodes. Lastly, the ecological network closure index (α), connectivity index (β), connectivity rate index (γ), and connectivity density index (ρ) after optimization of hydrological analysis grew to 0.84, 2.43, 0.89, and 0.16, respectively. This study can provide data support for optimizing the future ecological security pattern and bird diversity conservation in Foshan.